2011
DOI: 10.1007/s10343-011-0244-z
|View full text |Cite
|
Sign up to set email alerts
|

Five Years of Continuous Thaumetopoea processionea Monitoring: Tracing Population Dynamics in an Arable Landscape of South-Western Germany

Abstract: Within this paper we summarize the results of the Thaumetopoea processionea monitoring at two observation sites and try to interpret population dynamics from 2006 to 2010 considering meteorological data. Furthermore, observations on the behaviour of neonates associated with oak budburst are presented and discussed. in 2007 large larval colonies occurred and population densities peaked. Massive defoliation and larval migration due to food shortage were observed regularly leading to reduced female moth fecundity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…). However, if the high temperatures are a month later in April, they have a positive effect on damage area, indicating a positive effect on survival and feeding rates (Wagenhoff and Veit ). Lymantria dispar appears to be affected by March temperatures but with a delayed effect on damage in the subsequent year.…”
Section: Discussionmentioning
confidence: 99%
“…). However, if the high temperatures are a month later in April, they have a positive effect on damage area, indicating a positive effect on survival and feeding rates (Wagenhoff and Veit ). Lymantria dispar appears to be affected by March temperatures but with a delayed effect on damage in the subsequent year.…”
Section: Discussionmentioning
confidence: 99%
“…OPM is a univoltine species found in many countries across Europe (Groenen and Meurisse 2012) and is a major defoliator of oak trees (Wagenhoff and Veit 2011). The larvae live communally in nests and feed almost exclusively on the leaves of oak trees (Quercus spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Breuer et al . (2003a) demonstrated that Pherocon traps were more efficient than Delta traps at capturing male OPM moths, yet Wagenhoff and Veit (2011) utilized Delta traps successfully in a 5-year OPM monitoring programme in south-west Germany. Similarly, both Gries et al .…”
Section: Discussionmentioning
confidence: 97%
“…High populations of OPM have occurred in Belgium, Germany, Italy, and the Netherlands in recent years, which have resulted in serious defoliation of oak trees (Stigter et al ., 1997;Roversi, 2008;EFSA, 2009;Wagenhoff & Veit, 2011). In combination with other biotic factors (e.g.…”
Section: Introductionmentioning
confidence: 99%